Florence Nightingale - Alexander, Carol (New York : Children's Press, 2004)
The story of Florence Nightingale, who revolutionized hospital care and nursing in the nineteenth century.
Includes index.
Booklist
2.1
K-3
Keywords: Nightingale, Florence, -- 1820-1910 -- Juvenile literature; Nurses -- England -- Biography -- Juvenile literature; Nightingale, Florence, -- 1820-1910.; Nurses -- Biography; Nightingale, Florence, -- 1820-1910.; Nurses -- Biography